Distortion Theorem and Koebe Domain for Starlike Functions of Complex Order - Bolcal, Metin; POLATOĞLU, YAŞAR (İstanbul Kültür Üniversitesi Yayınları, 2002)
The aim of this paper is to give distorion theorem and Koebe domain for the class of starlike functaions of complex order under the conditions. |b|≤ (Re(1/b) -|Z| Re(1/b) -2|Z|²)/(2⎹z[Re(1/b)+( 2-Re(1/b) )]⎸), Re(1/b-1)>0,|Z|<1

Bu çalışmanın amacı |b|≤ (Re(1/b) -|Z| Re(1/b) -2|Z|²)/(2⎹z[Re(1/b)+( 2-Re(1/b) )]⎸), Re(1/b-1)>0,|Z|<1 koşulu altında kompleks mertebeden yıldızıl fonksiyonlar için yeni bir distorsiyon teoremi ve Koebe bölgesini vermektir.
Keywords: starlike functions of complex order; Karmaşık düzenin starlike işlevleri; distortion theorem; distorsiyon teoremi; koebe domain; Koebe etki; caratheodory functions; caratheodory fonksiyonları